Monocyte to high-density lipoprotein cholesterol ratio decreased in patients with psoriasis treated with ixekizumab - Funda Tamer; Fahrettin Kucukhemek; Ayla Gulekon (Permanyer, 2023)
Background: Monocyte to high-density lipoprotein cholesterol ratio (MHR) is a novel inflammatory biomarker which has been associated with cardiovascular diseases. Objective: To study MHR in patients with psoriasis treated with biological agents. Methods: Between April 2019 and August 2022, MHR was retrospectively evaluated in patients with psoriasis before and 3 months after treatment with infliximab, adalimumab, etanercept, ixekizumab, secukinumab, and ustekinumab in a university hospital in Ankara, Turkey. Results: This study included 128 patients, 53 females and 75 males. 39 (30.5%) patients were treated with infliximab, 26 (20.3%) with adalimumab, 8 (6.3%) with etanercept, 18 (14.1%) with ixekizumab, 12 (9.4%) with secukinumab, and 25 (19.5%) with ustekinumab. The median MHR was 0.0127 (0.0086-0.0165) in females and 0.0146 (0.0119-0.0200) in males (p = 0.011). The median MHR decreased after treatment with adalimumab, ixekizumab, secukinumab, and ustekinumab, whereas it increased after treatment with infliximab and etanercept (p = 0.790, p = 0.015, p = 0.754, p = 0.221, p = 0.276, p = 0.889, respectively). Conclusion: MHR significantly decreased in patients with psoriasis after treatment with ixekizumab. Since high MHR levels have been associated with poor clinical outcomes in patients with cardiovascular diseases, ixekizumab might have a positive impact in the treatment of psoriasis patients who had cardiovascular diseases. We suggest that MHR may be useful both in establishing appropriate biological agent treatment and in the follow-up of patients with psoriasis treated with biological agents.